PENGARUH VARIASI KEKERASAN DENGAN PENDINGIN BERBEDA TERHADAP KERUSAKAN MATA PISAU PEMBELAH BAMBU : THE EFFECT OF VARIATIONS IN HARDNESS WITH DIFFERENT COOLANTS ON BLADE DAMAGE BAMBOO SPLITTER - Nesta, Gatha (Jurnal Teknik Mesin, 2025)
This research is more in-depth about the difference coolant on bamboo splitting blade damage, the coolant used is (Water, Salt Water and Oil). The coolants used are (Water, Salt Water and Oil) Data collection using experimental method or experiments in this research laboratory include the use of tools and test specimens, after being used to split bamboo on the bamboo splitting machine. From the results of the hardening value of the cooling media Water is obtained average value of 296.416478 and the damage value obtained is an average of 2,38, from the the results of the hardening value of the Salt Water cooling medium obtained an average value of 296.3993112 and the average damage value is 3,50, from the results of the value of hardening of oil cooling media obtained an average value of 296.4512877 and the average damage value is 2,96.